Secular Christian schools : negotiating dogma and legislation in the Christian schools of Singapore - Tan, Desiree Yanzi (Nanyang Technological University, 2020)
This thesis explores the changes in the administration of Christian mission schools in Singapore and the challenges in negotiating dogma and legislation. I argue that while the schools had to compromise on certain structures expected of Christian mission schools, they are still ultimately in line with religious teachings and achieve the primary goal of establishing their mission schools in Singapore.